A comparative study of human and rat hippocampal low‐frequency oscillations during spatial navigation. Issue 8 (29th April 2013) - Watrous, Andrew J.; Lee, Darrin J.; Izadi, Ali; Gurkoff, Gene G.; Shahlaie, Kiarash; Ekstrom, Arne D.
ABSTRACT Rhythmic oscillations within the 3–12 Hz theta frequency band manifest in the rodent hippocampus during a variety of behaviors and are particularly well characterized during spatial navigation. In contrast, previous studies of rhythmic hippocampal activity in primates under comparable behavioral conditions suggest it may be less apparent and possibly less prevalent, or even absent, compared with the rodent. We compared the relative presence of low‐frequency oscillations in rats and humans during spatial navigation by using an oscillation detection algorithm ("P‐episode" or "BOSC") to better characterize their presence in microelectrode local field potential (LFP) recordings. This method quantifies the proportion of time the LFP exceeds both a power and cycle duration threshold at each frequency, characterizing the presence of (1) oscillatory activity compared with background noise, (2) the peak frequency of oscillatory activity, and (3) the duration of oscillatory activity. Results demonstrate that both humans and rodents have hippocampal rhythmic fluctuations lasting, on average, 2.75 and 4.3 cycles, respectively. Analyses further suggest that human hippocampal rhythmicity is centered around ∼3 Hz while that of rats is centered around ∼8 Hz. These results establish that low‐frequency rhythms relevant to spatial navigation are present in both the rodent and human hippocampus, albeit with different properties under the behavioral conditions tested. © 2013 Wiley Periodicals, Inc.